ANALISIS PENDAPATAN, RESIKO PRODUKSI DAN FAKTOR-FAKTOR YANG BERPENGARUH DALAM PENGAMBILAN KEPUTUSAN BERUSAHATANI PADI ORGANIK DAN ANORGANIK DI KABUPATEN PRINGSEWU - Fikri Syahputra; Zulkarnain Zulkarnain; Bigi Undadraja (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aims to analyze (1) the income of organic and anorganic rice farming, (2) the risk of organic and anorganic rice production, (3) the factors that influence the decision making of farmers to choose organic rice farming. The research was conducted in Pagelaran Village and Patoman Village, Pagelaran District, Pringsewu Regency. The sample in this study were 88 respondents consisting of organic and non-organic rice farmers. The method used is quantitative analysis and logistic regression. The results showed that (1) the income of organic rice farming was Rp 24.579.156,66 with an R/C value of 1,53 while anorganic rice farming was Rp 9.046.423,03 with an R/C value of 1,75. (2) The risk coefficient of organic rice farming production is 0,514 while anorganic is 0,608. (3) The variables that influence the decision making of organic rice farming are age and education level.